Reality and expression in the poetry of Carlos Pellicer - Melnykovich, George (North Carolina studies in the Romance languages and literatures, 1979)
This study explores the aesthetics of Pellicer's poetic vision of reality by treating the relationship between form and content in his poetry. The author creates a five-chapter volume that covers topics including Pellicer's poetic influencers, his understanding and expression of reality, and the way he portrays said reality.Volume211 in the North Carolina Studies in the Romance Languages and Literatures series.